2012
DOI: 10.1097/inf.0b013e318261130f
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Evidence for Transmission of HIV From Children to Breastfeeding Women and Implications for Prevention

Abstract: Background-Child-to-breastfeeding woman transmission (CBWT) of HIV occurs when an HIV-infected infant transmits the virus to an HIV-uninfected woman through breastfeeding. Transmission likely occurs as a result of breastfeeding contact during a period of epithelial disruption, such as maternal skin fissures and/or infant stomatitis. Despite extensive epidemiologic and phylogenetic evidence, however, CBWT of HIV continues to be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…Many of the studies on the impact of infant feeding methods and exposure to various ART regimens were conducted before the 2010 WHO PMTCT. [ 55 , 57 ] Although infant feeding results were available from only a minority of studies in this review, the results of the review are in agreement with the findings which led to the current guidelines. In the countries under review breastfeeding is very common, and breastfed infants have an increased risk of MTCT of HIV.…”
Section: Discussionsupporting
confidence: 74%
“…Many of the studies on the impact of infant feeding methods and exposure to various ART regimens were conducted before the 2010 WHO PMTCT. [ 55 , 57 ] Although infant feeding results were available from only a minority of studies in this review, the results of the review are in agreement with the findings which led to the current guidelines. In the countries under review breastfeeding is very common, and breastfed infants have an increased risk of MTCT of HIV.…”
Section: Discussionsupporting
confidence: 74%
“…11 Advice regarding breastfeeding is clearly a matter of concern. Previous studies have found that HIV and hepatitis B virus appear in breast milk and cause mother-to-infant transmission; 26,27 and that mothers with COVID-19 can transmit the virus through respiratory droplets or skin contact during breastfeeding. In contrast to a study that did not find SARS-CoV-2 in the breast milk of women with COVID-19, 7 we found a positive viral nucleic acid test in one breastmilk sample.…”
Section: Discussionmentioning
confidence: 99%
“…Practice of breastfeeding among the HIV positive mothers was high as majority of them perceived breast milk as beneficial to their infants, hence they breastfed their infants. Although current PMTCT guidelines promote exclusive breastfeeding as a feeding option for HIV-exposed infants (HEI), at the time of this study, HIV positive mothers were not encouraged to breastfeed in order to prevent transmission of the virus to their infants [ 25 , 26 ]. Breastfeeding of infants is a social norm among Africans, and some studies have reported that since mothers who failed to breastfeed their babies were suspected of having HIV, many HIV positive mothers choose to breastfeed their infants to prevent this suspicion and the resultant stigma [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%